Comparison between the Amazonian and oriental method of tapping rubber trees - Moraes, Vicente H.F. (Pesquisa Agropecuaria Brasileira, 2014)
A comparison was made between the current amazonian method of tapping wild rubber trees and the oriental tapping method, taking into consideration the peculiarities of the amazonian system of native rubber exploitation. Under comparable conditions, with Ethrel stimulated trees, the yield of the amazonian tapping method was statistically higher than the yield obtained with the oriental tapping method, probably due to the deeper but still safe cuts of the amazonian method, as particularly practiced in the reported experiment. The amazonian method offers certain advantages, irrespective of yield, such as: a better protection against panel diseases in the wetter atmosphere under the forest canopy, a faster regeneration of the tapped bark, the fact of its being easier to be made, and its already well established and widespread practice. Therefore, no advantages should be expected from a change to the oriental method in the current system of wild rubber production. Nevertheless, the faster bark consumption by the amazonian method renders it inappropriate to used in cultivated rubber trees, as they area tapped all the year round, without the 6-menth rest period of the wild rubber trees.